Visual Contracts as Test Oracle in AGG 2.0 - Khan, Tamim; Runge, Olga; Heckel, Reiko (Electronic Communications of the EASST, 2012)
A test oracle predicts expected outcomes for a set of test cases, often based on a formal, executable specification. Visual contracts are graph transformation rules describing pre- and post-conditions of a service’s operations. To obtain an oracle based on visual contracts, we use the Attributed Graph Grammar System (AGG) to execute the rules, creating a simulation of the behaviour expected of the system under test. The paper discusses the basic idea, illustrates it by an example, describes the challenges and solutions of its implementation and draws conclusions for the use of graph transformation and AGG in test oracles.